Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Ketepatan Waktu Pelaporan Keuangan - Lilis Handayani; Krisnhoe Sukma Danuta; Ginanjar Adi Nugraha (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of profitability, company size, and leverage on the timeliness of financial reporting. This research is quantitative research, using secondary data from financial statements. Purposive sampling method were used in this research, resulting 26 companies in basic manufacturing and chemical industrial sectors listed on the Indonesia Stock Exchange, 2016 to 2018 period as sample. Analysis of the data used in this study is logistic regression. The results show that the profitability has a significant positive effect on the timeliness of financial reporting, company size does not affect the timeliness of financial reporting, and leverage have significant negative effects to timeliness of financial reporting. This research can be used by the companies to improve their timeliness of financial reporting.